Pemanfaatan Platform Shopee Dalam Meningkatkan UMKM Di Desa Air Putih - Sari, Desti Rupita; Aprilia, Cindy; Ulandari, Resti; Mahmudi, M. Ikhawan; Abi, Yudi Irawan (Jurnal Gotong Royong, 2024)
The use of the shopee platfrom in improving MSME in Air Putih village aims to provide understanding to the community regarding the benefits of the Shopee application and is expected to encourage or advance MSME in Air Putih village, Margasakti Sebelat Sub-district, North Bengkulu District..